"The sum of two integers is 10" is: x + y = 10
"Three times the larger integer is three less than eight times the smaller integer" is 3x = 8y - 3 (where x is the larger integer and y is the smaller integer).
From the first statement, we can put x in terms of y: x = 10 - y
Plug "10 - y" for x in the second statement:
3(10 - y) = 8y - 3
30 - 3y = 8y - 3
33 = 11y
3 = y
Plugging the value of y into the first statement:
x + 3 = 10
x = 7
Your integers are 7 and 3.
2007-01-19 10:10:31
·
answer #1
·
answered by kimberlyjo_3 2
·
0⤊
0⤋
Let x and y be the two integers, and let y be the larger integer.
Then,
x + y = 10 ("The sum of two integers is 10.")
3y = 8x - 3 ("Three times the larger integer IS three less than 8 times the smaller integer.")
We have two equations, and two unknowns:
x + y = 10
3y = 8x - 3
Let's rearrange 3y = 8x - 3 so that it's in the same form as the other equation
x + y = 10
8x - 3y = 3
To solve this, we use substitution.
x + y = 10 means y = 10 - x.
Plugging in y = 10 - x into the second equation,
8x - 3(10 - x) = 3
Expand by distributing the -3 over the brackets,
8x - 30 + 3x = 3
Group like terms; move the -30 to the right hand side.
11x = 33
Divide both sides by 11, which gives you x = 3.
Now that you know x = 3, you can obtain y.
y = 10 - x, so y = 10 - 3 = 7
Your two integers are x = 3, y = 7.
2007-01-19 10:08:16
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
You need to set up two simultaneous equations. Assign variables to both
x = larger integer
y = smaller integer
Your first equation should look like this
X + Y = 10
Your second one will look like this
3X = 8Y - 3
Three times the larger integer = 3X
3 less than 8 times the smaller integer = 8Y - 3
Now rewrite the equation so that both variables are on one side
3X - 8Y = -3
You now have two equations to solve:
1) X + Y = 10
2) 3X - 8Y = -3
Multiply equation 1 by negative 3. It now looks like
-3X + -3Y = -30
Add this equation to equation 2. This will cancel out the X's leaving you with only one variable
-11Y = -33
Divide both sides by -11
Y = 3
Plug this back into equation number one and solve for X
X = 7
2007-01-19 10:09:32
·
answer #3
·
answered by Nick G 1
·
0⤊
0⤋
Write down all the facts
x + y = 10
8y - 3x = 3
isolate a variable
x = 10 - y
substitute the variable u isolated
8y - 3(10 - y) = 3
8y - 30 + 3y = 3
11y = 33
y = 3
therefore x = 7
x = 7; y = 3
2007-01-19 10:11:32
·
answer #4
·
answered by Donny Dutch 4
·
0⤊
0⤋
2 integers x and y
x+y=10 =>x=10-y
Assume x largest: 3*x+3=8*y
=>3*(10-y)+3=8*y=>30-3*y+3=8*y
=>11*y=33
=>y=3 and x=10-3=7
2007-01-19 10:06:18
·
answer #5
·
answered by iron_pennywise 1
·
0⤊
0⤋
for bicycle proprietor #a million, distance travelled is X; fee is 17mph for bicycle proprietor#2. distance travelled is (fifty 4-X); fee is nineteen mph from Distance=(fee)(time); time=Distance / fee by way of fact the time for the two bicycle proprietor to fulfill is the comparable, as a result; .....17/X = 19/(fifty 4 - X) and X=25.5 miles travelled for bicycle proprietor #a million as a result; for bicycle proprietor #a million 17mph/25.5mi = 0.6666666hours =40 minutes and for bicycle proprietor #2, 54mi -25.5mi = 28.5 mi distance travelled back 19mph/28.5mi = 0.666666hours =40 minutes as a result it extremely is a million:40 pm while the bicycle proprietor met.
2016-12-16 08:39:02
·
answer #6
·
answered by ? 4
·
0⤊
0⤋